Impact Of Multidisciplinary Maternal Resuscitation Training Program on Improving the Front-Line Care Provider’s Readiness to Manage Maternal Cardiac Arrest: A Pre-test/Post-test Study - Mohamed Elsayed Saad Aboudonya (18466385) (2024)
Background Maternal Cardio-Pulmonary Resuscitation (CPR) is a crucial emergency multidisciplinary intervention for resuscitating a pregnant woman who experiences cardiac or respiratory arrest. Early and appropriate multidisciplinary maternal resuscitation can reduce maternal fatalities and enhance maternal and newborn outcomes. Hamad International Training Center not only offers formal resuscitation training like Advanced Life Support Obstetrics and Neonatal Resuscitation Program courses but also ensures the frontline care providers’ readiness for managing cardiac arrest events in Hamad Medical Corporation facilities through regular mock drills and monitoring the relevant Key Performance Indicators (KPIs). The study aimed to explore the impact of a multidisciplinary maternal resuscitation training program and the introduction of the maternal resuscitation algorithm pathway (Figure 1) on the relevant seven KPIs. Methods A pre-test/post-test design was implemented to evaluate the healthcare professionals' readiness to manage obstetric cardiac arrests. The sample size consisted of three groups of front-line multidisciplinary obstetric maternal resuscitation teams (physicians, midwives, and nurses) divided into a pre-test group (N=30) and post-test group (N=30). The multidisciplinary resuscitation teams were observed during the cardiac arrest mock drills both before and after conducting the multidisciplinary resuscitation simulation-based training program and the introduction of the maternal resuscitation algorithm pathway against seven KPIs. Those KPIs were Time to Confirm Cardiac Arrest; Code Blue and /or Code White Activation Time; Time to attempt first chest compression; Defibrillator Arrival Time; Time to First Defibrillation shock; Code blue/code white arrival time and Time to perform Perimortem Caesarean Delivery. Results The descriptive and inferential data analysis (Table 1) reflected that four out of the seven KPIs had a significant improvement after conducting the training program. Conclusion The study helped to determine that integrating multidisciplinary maternal resuscitation simulation-based training with formal resuscitation courses and introducing a clear maternal resuscitation algorithm improved frontline staff readiness to manage maternal cardiac arrests.